Enhancing Mathematics Learning Outcomes in Circle Unit through Cooperative Learning with Team Game Tournament via Quizizz and Math Learning Center Applications for Grade 6 Students (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research focused on two main objectives. 1) Comparing learning achievement of the learning in Circle unit, before and after learning by using the cooperative learning method with Team Game Tournament technique via Quizizz and Math Learning Center applications of Grade 6 students. 2) Examining students’ satisfaction towards collaborative learning management by using the cooperative learning method with Team Game Tournament technique via Quizizz and Math Learning Center applications of Grade 6 students. This research involved a sample group of 42 grade 6 students from Class 6/1 at Maneewattana School, selected by using cluster sampling. The study employed three main research instruments. 1) the cooperative learning management plan with Team Game Tournament technique, 2) the achievement test, and 3) the satisfaction questionnaire. The statistics used in data analysis were mean, standard deviation and t-test Dependent. The research findings revealed that 1) students who learned through the cooperative learning method with the Team Game Tournament using the Quizizz and Math Learning Center applications had higher academic achievement scores after studying (Mean = 15.79, S.D.= 2.02) than before studying (Mean = 9.10, S.D.= 2.31) at a statistical significance level of .05, and 2) students’ satisfaction with the cooperative learning method using the Team Game Tournament through the Quizizz and Math Learning Center applications was at a high level (Mean = 3.83, S.D. = 0.70).